Energy audit of building systems : an engineering approach - Krarti, Moncef (Boca Raton, FL. : CRC Press, 2011)
'The second edition of a bestseller, this book offers a systematic engineering approach to a wide range of measures and opportunities for saving energy and reducing operating costs in residential and commercial buildings. The author provides general tools and procedures for performing building energy audits, including economic analysis, building energy simulation, and field testing. His focus then turns to various subsystems, exploring the techniques and technologies that can reduce energy use or operating costs. Each chapter includes simplified calculation methods used to evaluate the effectiveness of various efficiency measures'--
Includes bibliographical references and index.
Keywords: Buildings -- Energy conservation; Energy auditing